Newsgames in Ecuador - Marín Gutiérrez, Isidro (2018)
Video games have been created on political and social issues since the beginning of this medium. In recent years, many computer developers are creating and launching games quickly in response to current events. These games are known as “newsgames”. Increasingly the number of Internet users increases using the network to consume news. Newsgames could become an important part of how people understand current events and could be an important and expressive genre of video games. Digital journalism is making the media look for new ways to tell news and interact with their audience. A journalist should use Information and Communication Technologies (ICT) and implement new journalistic formats. In Ecuador this process takes time to boot although some media are putting these formats into practice as is the case of newsgames. Our work studies the newsgames that are being produced in Ecuador.